2003
DOI: 10.1002/pros.10305
|View full text |Cite
|
Sign up to set email alerts
|

Genomic scan of 254 hereditary prostate cancer families

Abstract: Hereditary prostate cancer (HPC) is a genetically heterogeneous disease, complicating efforts to map and clone susceptibility loci. We have used stratification of a large dataset of 254 HPC families in an effort to improve power to detect HPC loci and to understand what types of family features may improve locus identification. The strongest result is that of a dominant locus at 6p22.3 (heterogeneity LOD (HLOD) = 2.51), the evidence for which is increased by consideration of the age of PC onset (HLOD = 3.43 in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
61
1
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 58 publications
(66 citation statements)
references
References 68 publications
3
61
1
1
Order By: Relevance
“…Janer et al (47) observed a peak LOD score at marker D7S2212 on 7q21 by using a recessive parametric model, with an HLOD of 2. 25 (LOD ϭ 1.55).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Janer et al (47) observed a peak LOD score at marker D7S2212 on 7q21 by using a recessive parametric model, with an HLOD of 2. 25 (LOD ϭ 1.55).…”
Section: Discussionmentioning
confidence: 99%
“…In late 2003, eight additional genomewide scans for prostate cancer susceptibility loci were reported, including our own studies of 254 Prostate Cancer Genetic Research Study (PROGRESS) and 188 Johns Hopkins University (JHU) families (47,48). The aggregate results are summarized in a review by Easton et al (49).…”
mentioning
confidence: 99%
“…Slager and colleagues (39), using Gleason grade as a quantitative trait, also found a suggestive linkage signal in this same region. Other groups reported linkage on chromosome 6, but at some distance from this locus (14,16).…”
Section: Meta-analysis For Finding Prostate Cancer Locimentioning
confidence: 89%
“…33). In this study, we used clinical data from 784 affected men from 248 HPC families for whom a genomic screen had been previously done (16). Disease characteristics such as Gleason score, stage, and PSA were used to classify affected men into categories of clinically insignificant, moderate, or aggressive prostate cancer.…”
Section: Family Studies For Genetic Mapping Of Prostate Cancer Locimentioning
confidence: 99%
See 1 more Smart Citation